Differences in health-related quality of life, neuropsychological functions and emotional state between children and adolescents with mild traumatic brain injury and healthy controls - Gutiérrez Ruiz, Karol; Luna Audivett, Diana; Mosquera Valoy, Yoissy (Revista de Psicopatología y Psicología Clínica, 2022)
Abstract: Little is known about the impact of mild traumatic brain injury (TBI) on the functioning of children in Latin America, especially regarding a broad construct called health-related quality of life (HRQoL). The objective of this study was to analyze the differences in HRQoL, neuropsychological functions and emotional state between a group of children and adolescents with mild TBI and a healthy control group. A case-control study was conducted in which 30 children and adolescents with mild TBI and their parents and a group of 30 healthy subjects participated. The results showed that participants with mild TBI had an HRQoL similar to the one of the general population of the same age and sex. At the cognitive level, the group with mild TBI had a lower processing speed and less work done in selective and sustained attention tasks; at the emotional and behavioral level, they exhibited more symptoms of anxiety, depression, withdrawal and social problems. Keywords: Traumatic brain injury; health-related quality of life; neuropsychological functions; emotional state. Diferencias en la calidad de vida relacionada con la salud, las funciones neuropsicológicas y el estado emocional entre niños y adolescentes con daño cerebral traumático leve y controles sanos Resumen: Se sabe poco sobre el impacto del trauma craneoencefálico (TCE) leve en el funcionamiento de los niños en Latinoamérica, especialmente en un constructo amplio denominado calidad de vida relacionada con la salud (CVRS). El objetivo de este estudio fue analizar las diferencias en la CVRS, las funciones neuropsicológicas y el estado emocional de un grupo de niños y adolescentes con TCE leve y un grupo control sano. Participaron 30 niños y adolescentes con TCE leve y sus padres, y un grupo de 30 sujetos sanos. Los resultados evidenciaron que participantes con TCE leve percibieron una CVRS similar a la población general de la misma edad y sexo. A nivel cognitivo el grupo con TCE leve tuvo una menor velocidad de procesamiento y cantidad de trabajo realizado en tareas de atención selectiva y sostenida; y a nivel emocional y conductual presentó mayor nivel de síntomas de ansiedad, depresión, retraimiento y problemas sociales. Palabras clave: trauma craneoencefálico; calidad de vida relacionada con la salud; funciones neuropsicológicas; estado emocional.